Indole glucoalkaloids from Chimarrhis turbinata and their evaluation as antioxidant agents and acetylcholinesterase inhibitors - Cardoso, C. L.; Castro-Gamboa, I; Silva, DHS; Furlan, Maysa [UNESP]; Epifanio, R. D.; Pinto, Abedala Derbli [UNESP]; de Rezende, C. M.; Lima, J. A.; Bolzani, Vanderlan da Silva [UNESP] (Amer Chemical Soc, 2004)
As part of our study on bioactive agents from Brazilian rainforest plants, two new glucoalkaloids, 3,4-dehydro-strictosidine (1) and 3,4-dehydro-strictosidinic acid (2), were isolated from Chimarrhis turbinata, along with seven known glucoalkaloids, cordifoline (3), strictosidinic acid (4), strictosidine (5), 5alpha-carboxystrictosidine (6), turbinatine (7), desoxycordifoline (8), and harman-3-carboxylic acid (9). The structures of the new alkaloids were established on the basis of comprehensive spectral analysis, mainly 1D and 2D NMR experiments, as well as high-resolution HRESIMS. Alkaloid 3 showed strong free-radical scavenging activity against 1,1-diphenyl-2-picrylhydrazyl (DPPH) as well as pronounced antioxidant activity evidenced by redox properties measured by ElCD-HPLC. Additionally, alkaloids 1-9 were submitted to TLC screening for acetylcholinesterase inhibitors. Both 7 and 8 were shown to be moderate acetylcholinesterase inhibitors at a concentration of 0.1 and 1.0 muM, respectively. In an in vitro rat brain assay, 7 showed moderate activity (IC50 1.86 muM), compared to the standard compound, galanthamine (IC50 0.92 muM).